حمض البول وعلاقته بالوظيفة الانبساطية للبطين الأيسر عند مرضى اعتلال العضلة القلبية التوسعي خبرة مشفى الأسد الجامعي باللاذقية بين عامي 2002-2003 - بله حسـام; رضوان عبد الناصر; منصور كنان (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 70 مريضاً بقصور قلب احتقاني ناجم عن اعتلال عضلة قلبي توسعي بمختلف أسبابه (البدئية والثانوية) راجعوا مشفى الأسد الجامعي باللاذقية خلال عام 2003. حيث خضع كل مريض لمجموعة من الاجراءات التشخيصية من فحص سريري دقيق ومجموعة من التحاليل المخبرية تشمل حمض البول. كما خضع كل مريض لإجراء ايكو قلب ودوبلر لتقييم وظيفة العضلة القلبية الانقباضية من خلال قياس الكسر القذفي EF والوظيفة الانبساطية من خلال قياس كل من E/A وزمن تقاصر الموجة E (DTE). وقُسِّم المرضى إلى مجموعتين من حيث الوظيفة الانبساطية: 1- مرضى لديهم نموذج امتلاء تاجي تحددي Restrictive Mitral Filling Pattern (RMFP) وهم يحققون واحدا مما يلي: - إما E/A < 2. - أو E/A = (1-2) و140 > DTE ميلي ثانية. 2- مرضى ليس لديهم نموذج امتلاء تاجي تحددي RMFP. ثم قورنت مستويات حمض البول عند كل مجموعة فكانت النتائج التالية: أن معظم أسباب قصور القلب الاحتقاني الناجم عن اعتلال عضلة قلبية توسعي (البدئي والثانوي) كانت الأسباب الاقفارية وشكلت حوالي 85.71% من المرضى وكان 20% من المرضى لديهم نموذج امتلاء تاجي تحددي وكان تركيز حمض البول عندهم (8.73±1.14) ملغ/100 مل P 0.5 > مع العلم ن التركيز المعياري لحمض البول (4.5±2.5) ملغ%مل مع اهمال الفرق بين النساء والرجال. وكان لقيم حمض البول عند هذه المجموعة علاقة عكسية مع DTE وعلاقة طردية مع نسبة E/A ولم نشاهد أية علاقة بين قيم حمض البول والكسر القذفي للبطين الأيسر (LVEF). This study included (70) patients of congestive heart failure as a result of dilated cardiomyopathy of different etiologies (primary – secondary) in Al-Assad University Hospital in Lattakia during 2003. Every patient submitted to some diagnostic procedures as exact clinical examination and some laboratory examination as uric acid. Patients were submitted to echo Doppler examination with measurement of mitral E wave and mitral A wave velocities, E/A ratio, E wave deceleration time DTE, ejection fraction. Patients were divided into two groups according to diastolic function. First group: Patients with Restrictive Mitral Filling Pattern (RMFP), they were marked by either E/A ratio > 2 or E/A ratio = (1-2) and DTE < 140 mill seconds. Second group: Patient without RMFP. Uric acid levels were compared within each group and we got the following results:. Most of congestive heart failure causes as a result of dilated cardiomyopathy (primary – secondary) were ischemic causes, about 85.71% and 20% of patients had Restrictive Mitral Filling Pattern and concentration of serum uric acid was [(8.73±1.14) mg/100 ml, P < 0.5], standard value [(4.5±2.5) mg/100 ml ((the difference between male and female was ignored)). Uric acid levels – in this group – was inverse relationship with declaration time of E wave and direct relationship with E/A ratio. There was no correlation between uric acid and Left Ventricular Ejection Fraction.